2017
DOI: 10.1186/s40510-016-0158-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting dental biofilm in patients wearing fixed orthodontic appliances

Abstract: BackgroundThe aim of this study is to investigate the amount and the distribution of biofilm in patients wearing fixed appliances and its relation with age, gender, frequency of tooth brushing, and patient motivation.MethodsThe sample comprised 52 patients (15.5 ± 3.6 years old, 30 females and 22 males) wearing fixed orthodontic appliances. Dental biofilm was assessed using a modified plaque index (PI). A questionnaire was used to collect patient’s information, including gender, age, treatment motivation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 24 publications
1
36
0
7
Order By: Relevance
“…Currently, there are limited data about oral hygiene habits among patients receiving orthodontic treatment in Lithuania. Moreover, adolescents tend to maintain a lower quality of tooth brushing and to have more dental plaque than adults [32]. Thus, it is essential to assess oral hygiene habits among adolescents receiving orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are limited data about oral hygiene habits among patients receiving orthodontic treatment in Lithuania. Moreover, adolescents tend to maintain a lower quality of tooth brushing and to have more dental plaque than adults [32]. Thus, it is essential to assess oral hygiene habits among adolescents receiving orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies suggest that females have better attitudes and habits toward oral hygiene than males due to a greater interest in their appearance [50]. Males tend to have significantly more dental plaque than females [32]. In addition, another study showed that a significantly higher gingival bleeding was observed among males [46].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown that patients wearing fixed orthodontic appliances present the highest accumulation of bacterial plaque in the gingival margin and behind the archwires of the maxillary lateral incisors and canines. The frequency of tooth brushing and the motivation for the orthodontic treatment is significantly associated with a reduction of dental biofilm in subjects undergoing fixed orthodontic therapy [12].…”
Section: Introductionmentioning
confidence: 99%
“…La falta de motivación y comunicación tiene un efecto negativo en el mantenimiento de la higiene oral (Mei et al, 2017). La evidencia científica ha demostra-do que los recordatorios activos son un mecanismo importante para producir cambios positivos en el comportamiento del paciente con respecto al tratamiento (Eppright et al, 2014;Lima et al, 2018).…”
Section: Introductionunclassified